Estereótipos de gênero e julgamento de adolescentes sobre profissões - Santos, Erica Karine Santana (2021)
Every year, thousands of students submit to the selection processes for entry to college, which are marked by professional and career choice. It is important to point out that the professional choice is multifactorial, including social, economic, political and family variables. In this sense, gender has been pointed out as a relevant variable to be studied, given that the phenomenon of connection between certain professions and gender has been historically demarcated in society according to the assignment of gender roles. From this perspective, this research was carried out to analyze how gender stereotypes influence adolescents' judgments about the existence of male and female professions. Three studies were conducted to achieve the objective. The first study was an integrative literature review of articles published between 2013 and 2018 in Bvs Psi, Lilacs, PePsic and Scielo; which aimed to map and review the Brazilian scientific production about gender in professional and career choices. The debate pointed to the fact that social constructions about gender roles contribute to the development of beliefs about professions, which leads to the idea that there are "female professions" and "male professions". The second study sought to find evidence of the validity of the Inventory of Ambivalent Sexism (ISA) for application to adolescents. To this end, a psychometric study was conducted through an online survey in which 486 adolescents of different socio-demographic profiles participated, aged 14 to 23. The results were satisfactory, since the scale presented adequate psychometric properties for use with the sample in question. The third study analyzed the influence of gender stereotypes in the judgment of professions seen socially as male or female, from the perspective of adolescents in the process of professional choice. The data collection, which included 486 participants, was conducted through an online survey, where participants responded to four instruments, including the scale validated in the previous study. The results pointed to a rigidity in gender stereotypes, since adolescents were more favorable when the occupation of the position followed a normative pattern and rejected the fact that a woman occupies a socially masculine profession. It is hoped that this dissertation will contribute to the development of future interventions with adolescents in educational settings, with a view to demystifying the effects of gender stereotypes on professions.